Participatory simulations of competing aquacultural and agricultural land uses in Bac Lieu Province, Mekong Delta, Vietnam - Dung, L.C.; Le Page, C.; Hoanh, Chu Thai (2007)
Rice and black tiger shrimp (Penaeus monodon) are produced in coastal area of the Mekong, Vietnam under different patterns depending on biophysical and social economic conditions. In the north part of Bac Lieu province in the Mekong Delta, competitions for land used among these farming systems have been appeared. Rice and shrimp rotation farming has been gradually encroached by shrimp monoculture due to its higher economic return. Monoculture of shrimp in a large scale however would hardly reach sustainability. This study aims to make explicit the criteria used by local producers in choosing their land use. To collectively discuss about these criteria and to build a common understanding of this complex agro-hydro system, we have been using roleplaying games (RPGs). Three RPG sessions have been organized in three selected villages in Bac Lieu coastal province in the Mekong Delta (i) to understand the competition of land used between rice and shrimp production at a village level; (ii) to understand decision making of farmers under complex biophysical and socio-economic conditions. By playing their own role during a RPG session, local farmers are embedded in participatory simulation. Following the companion modeling approach, the next methodological step will consist in implementing an agent-based model to formalize the shared representation that was built during RPG sessions. Local farmers are then expected to be comfortable in following and discussing computer simulations as they will be able to relate the "agent-based simulations" to what they have experienced as participants of "players-based simulations" (the RPG sessions).